2017
DOI: 10.1111/jar.12395
|View full text |Cite
|
Sign up to set email alerts
|

The transition to adulthood of young adults with IDD: Parents’ joint projects

Abstract: Parents act together and with others relative to the transition to adulthood of their young adult children with IDD. These projects are complex and differ in goals, steps, resources and emotional regulation and motivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…Qualitative methods were used in 25 studies. While most studies did not specify their framework or paradigm, five studies employed the phenomenological method (Davys, Mitchell, & Haigh, ; Gauthier‐Boudreault, Couture, & Gallagher, ; Holl & Morano, ; Knox & Bigby, ; Walker & Hutchinson, ) and two studies conducted action research (Craig & Cartwright, ; Young et al, ). Most ( n = 18) studies included individual interviews.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative methods were used in 25 studies. While most studies did not specify their framework or paradigm, five studies employed the phenomenological method (Davys, Mitchell, & Haigh, ; Gauthier‐Boudreault, Couture, & Gallagher, ; Holl & Morano, ; Knox & Bigby, ; Walker & Hutchinson, ) and two studies conducted action research (Craig & Cartwright, ; Young et al, ). Most ( n = 18) studies included individual interviews.…”
Section: Resultsmentioning
confidence: 99%
“…There may be two reasons for the lack of qualified professionals: lack of empathy and high turnover rate. Regarding the former, professionals may not be able to relate and understand the experience of parenting an individual with IDD (Young et al, ). Indeed, many parents have reported that professionals did not have empathy for their situations.…”
Section: Resultsmentioning
confidence: 99%
“…Then, we use the transition to adulthood as an illustration of how CAT has been used to conceptualize the design of research and the actionproject method (A-PM) to reflect that design. We conclude by presenting an integration of findings from several recent studies on the transition to adulthood conducted by Young and colleagues (e.g., Young et al, 2008Young et al, , 2011aYoung et al, , 2017. Findings from these studies demonstrate the unique contribution of CAT and the A-PM for an integrative, processoriented understanding of human action.…”
Section: Introductionmentioning
confidence: 67%
“…To date, research using the A-PM to study the transition to adulthood has sought to describe and understand the intentional, goal-directed processes young people and their parents , counsellors (Young et al, 2011a), and peers engage in during the transition to adulthood. Additional studies have addressed: (a) the types of projects for future work and life together that young adults involved in a committed relationship jointly construct and pursue ; and (b) the joint goal-directed actions and projects of parents, and siblings taking on parental roles, as young adults with intellectual or development disabilities (IDD) were making transitions to adulthood (Young et al, 2017). In all of these studies, attention to the description of findings was on the sample as a whole and on the main patterns of action identified across participants, that is, on important joint projects and on the superordinate joint transitional projects engaged in by participants (youth or parents) and those involved with them.…”
Section: Joint-goal Directed Processes Inherent To the Transition To mentioning
confidence: 99%
See 1 more Smart Citation